Donor Bank ASI dalam Pandangan Islam dan Kesehatan - Titin Setiawati; Wahyu Pudjiastuti (Masterpiece: Journal of Islamic Studies and Social Sciences, 2026)
Breast milk donation is a medical and social solution for babies who cannot get breast milk directly from their biological mothers. This practice is increasingly growing in Indonesia along with the increasing awareness of the importance of exclusive breastfeeding. However, from an Islamic perspective, breast milk donation is not just a medical issue, but also concerns aspects of sharia law, mahram relations, and protection of lineage. This article examines breast milk donation in depth from an Islamic perspective, covering sharia arguments, fatwas from scholars, legal provisions, and implementation challenges in modern society. Abstraksi Donor Air Susu Ibu (ASI) merupakan solusi medis dan sosial bagi bayi yang tidak dapat memperoleh ASI langsung dari ibu kandungnya. Praktik ini semakin berkembang di Indonesia seiring meningkatnya kesadaran akan pentingnya ASI eksklusif. Namun, dalam perspektif Islam, donor ASI tidak sekadar persoalan medis, melainkan juga menyangkut aspek hukum syariah, hubungan kemahraman, dan perlindungan nasab. Artikel ini mengkaji donor ASI secara mendalam menurut pandangan Islam, mencakup dalil-dalil syar'i, fatwa ulama, ketentuan hukum, serta tantangan implementasi di masyarakat modern.